Ending the Shell Game: White-Collar Crime in the Light of Theoretical Approach and Battling its Emerging Threat in Pakistan - Butt, Muhammad Zaman (Law and Policy Review, 2022)
This study intends to explore the situation of white-collar crime that currently exists in Pakistan and suggests appropriate measures to combat this perpetuating crime by reforming laws and by providing transparent access to law enforcement agencies. For this purpose, the author carried out a deep analysis of the various white-collar crimes using different theoretical approaches. Furthermore, the author stressed the effect of white-collar crimes on the country’s economy. The nature of crime has evolved in numerous ways as civilization has advanced. Despite categorizing crimes in different types on multiple bases, criminal jurisprudence has designated them as white-collar crimes.